The Benefits of Insomnia Treatment Using an Herbal Combination Pao Fuzi, Renshen, Baizhu, Ganjiang, and Zhigancao - Ie Sien, Lim; Ang, Suryawan (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Insomnia is a disorder that causes sufferers to have trouble sleeping or not be able to sleep properly. Insomnia can affect physical and mental health, resulting in suboptimal quality of life and daily routines. Insomnia is usually followed by daytime sleepiness, accompanied by fatigue, speechlessness, irritability, sweating alone, and a depressed mood. Herbal medicine therapy is an alternative that can be used to treat insomnia. Objective: The purpose of this study was to determine the effectiveness of Pao Fuzi, Renshen, Baizhu, Ganjiang, and Zhigancao for medication therapy in insomnia sufferers with the syndrome. Method: This research uses the case study research method. The research subject is Mr. Y, who has insomnia with spleen and kidney deficiency syndrome. Result and Discussion: The results of research using the combination herbs for insomnia sufferers have proven effective. The Insomnia Severity Index (ISI) score before therapy was 28 and after therapy was 3. Complaints of insomnia decreased gradually, and the quality of life became better. Conclusion: Besides that, sufferers had no difficulty starting to sleep again, and when he woke up, he felt more refreshed